The Correlation of Eigth Grade Students’ Confidence Level and Speaking Skill at SMP YAPIPA Serpong, Tangerang - Laras - Sati; Nargis Nargis Nargis; Abdul - Rohim (Globish: An English-Indonesian Journal for English, Education, and Culture, 2019)
This research aim to find out the correlation between students’ confidence level and their speaking skill on the eigth grade students of SMP YAPIPA. The research was conducted at SMP YAPIPA, the subject of this research was the students on the eigth grade in class VIII A have 31 students and  VIII B have 34 students. The total of the respondents are 65 students. In this research the researcher used quantitative survey research. Technique collecting data in this research with using quesionnaries confidence level consist of 64 questions and monologue for speaking test. The regression significance test it cound be seen that the score of F were 0.342 and the significant were 0.561, the df 1:63 = 64 (4.00) in significant 5% the explanation 0.342< 0.561. The result of tobserve was about 0.589 and ttable result were 1.99. If the result (0.561 < 1.99) means there is no significant correlation between students’ confidence level and speaking skill.Keyword:       Students’ confidence level, Speaking Skill, Monologue Speaking test